Sebaran Kandungan Logam Berat Di Perairan Pulau Sulawesi Dan Dampaknya Bagi Kesehatan: Literatur Review - Matius Paundanan; Sitti Ainun Hikmah; Nely Zulfa (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2026)
Sulawesi Island has a long coastline with abundant marine resources. However, rapid coastal development, increasing urbanization, and various anthropogenic activities such as mining, port operations, and waste disposal have heightened the burden of heavy metal pollution. This study reviews the spatial distribution of heavy metals and their impact on the health of coastal communities in Sulawesi based on scientific publications from 2009–2025. The heavy metals examined include Hg, Pb, Cd, Cr, Cu, As, Fe, Ni, and Zn in marine, river, and lake waters. A review of 32 studies revealed that the highest concentrations of heavy metals were found in areas with intense human activity, such as Pare Bay, the Makassar Coast, Kendari Bay, and the Bone River in Gorontalo. Pb and Cd levels in several sites exceeded environmental quality standards, indicating potential risks to aquatic biota and human health. The bioaccumulation of heavy metals in fish and marine organisms can lead to neurological and kidney disorders as well as degenerative diseases. Cross-sectoral monitoring, regulatory enforcement, and community education are needed to mitigate exposure risks. This review serves as a foundation for environmental management policies and health risk mitigation related to heavy metal exposure.